Meniscal allograft transplantation - Packer, J. D.; Rodeo, S. A. (Clinics in Sports Medicine, 2009)
Meniscal allograft transplantation has emerged as a treatment option for selected meniscus-deficient patients to restore normal meniscal function and forestall progressive joint degeneration. Contraindications include diffuse subchondral bone exposure, axial malalignment, and instability. However, a knee may be rendered suitable for meniscus transplantation if combined with chondral resurfacing, osteotomy, and/or ligament reconstruction. Although numerous studies have reported improved clinical outcomes with meniscal allograft transplantation, high-quality studies with control groups are lacking in the literature. This article describes the current indications, graft types and sizing, surgical techniques, and a review of the literature with a focus on the role of concomitant procedures.